Synthetic peptides derived from the C-terminal region of Lys49 phospholipase A2 homologues from Viperidae snake venoms: biomimetic activities and potential applications - Lomonte, Bruno (2010)
Lys49-phospholipase A2 homologues constitute a large family of toxins present in the venoms of viperid snake species, which despite lacking catalytic activity, cause significant skeletal muscle necrosis. The main structural determinants of this toxic effect have been experimentally mapped to a region near their C-terminus (115-129), which combines cationic and hydrophobic/aromatic amino acid residues. Short (13-mer) synthetic peptides representing this C-terminal region can mimick several of the effects of Lys49 PLA2 homologues. In addition to their ability to damage muscle cells, these peptides display antibacterial, antiendotoxic, antifungal, antiparasite, and antitumor activities, as well as VEGF-receptor 2 (KDR)-binding and heparin-binding properties. Modifications of their sequences have shown possibilities to enhance their effects upon prokaryotic cells, while decreasing toxicity for eukaryotic cells. This review presents an updated summary on the biomimetic actions exerted by such peptides, and highlights their potential value as molecular tools or as drug leads in diverse biomedical areas.